Home Literacy Experiences and Their Relationship to Bilingual Preschoolers' Developing English Literacy Abilities: An Initial Investigation - Hammer, Carol Scheffner (Lang Speech Hear Serv Sch, 2003)
PURPOSE: This study investigated the relationship between home literacy experiences and bilingual pre-schoolers' early literacy outcomes. METHOD: Forty-three Puerto Rican mother–child dyads recruited from Head Start programs in central Pennsylvania participated in this study of home literacy experiences and emerging English literacy abilities. The dyads were grouped according to whether the children had learned Spanish and English from birth (simultaneously; n = 28) or Spanish from birth and English in Head Start (sequentially; n = 15). Mothers of simultaneous and sequential learners were compared on the value they placed on literacy, press for achievement, the number of reading materials that were available in the home, and how often they read to their child. The children were compared on their scores on the Test of Early Reading Ability–2 (Reid, Hresko, & Hammill, 1991), which was given during the first and second years of their Head Start program. RESULTS: Mothers of simultaneous and sequential learners differed with regard to mothers' press for achievement. No differences were found between the two groups with respect to the other measures. When the early literacy abilities of the two groups of children were assessed, all learners had comparable mean emergent reading scores. The mean literacy scores of the entire group of children were significantly lower at Year 2 as compared to Year 1. CLINICAL IMPLICATIONS: Although the children experienced literacy activities at home and in Head Start, it appears that children's literacy development would benefit from increased exposure to literacy materials and literacy events during the preschool years.